Karawajew’s ant type specimens (Hymenoptera, Formicidae) in the National Museum of Natural History of the National Academy of Sciences of Ukraine - Martynov, Alexander V.; Radchenko, Alexander G. (Zootaxa, 2016)
The collection of W.A. Karawajew is one of the richest and most famous ant collections of the World. Much of this collection consists of dry mounted specimens, including types of about 550 taxa, housed in the Shmalhausen Institute of Zoology of the National Academy of Sciences of Ukraine (Kiev). Nevertheless, we located a considerable part of Karawajew’s collection, containing about 25,000 specimens in alcohol, that is preserved in the National Museum of Natural History of the National Academy of Sciences of Ukraine (Kiev). The latter material was recently examined and we found types of 24 taxa. This type material was partly mounted, re-ordered and catalogued. In this paper we present a catalogue of these type specimens housed in the National Museum of Natural History.